2013
DOI: 10.5051/jpis.2013.43.6.262
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation and implants: implications for dentistry

Abstract: The use of dental implants has become a mainstay of rehabilitative and restorative dentistry. With an impressive clinical success rate, there remain a few minor clinical issues with the use of implants such as peri-implant mucositis and peri-implantitis. The use of laser technology with implants has a fascinating breadth of applications, beginning from their precision manufacturing to clinical uses for surgical site preparation, reducing pain and inflammation, and promoting osseointegration and tissue regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…Although the exact molecular mechanism is not fully understood, significant clinical effects including analgesia, reduced inflammation and accelerated wound healing are well known [186,187]. A recent review and several previous research articles in animal models have highlighted the potential of PBM to improve dental implant stability by increasing osteocyte viability, osteoclast proliferation and improving bone repair and osseintegration [171,[188][189][190], although there exist limited randomized clinical trials in this area.…”
Section: Laser Therapy Photodynamic Therapy and Photobiomodulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the exact molecular mechanism is not fully understood, significant clinical effects including analgesia, reduced inflammation and accelerated wound healing are well known [186,187]. A recent review and several previous research articles in animal models have highlighted the potential of PBM to improve dental implant stability by increasing osteocyte viability, osteoclast proliferation and improving bone repair and osseintegration [171,[188][189][190], although there exist limited randomized clinical trials in this area.…”
Section: Laser Therapy Photodynamic Therapy and Photobiomodulationmentioning
confidence: 97%
“…Applications include fabrication and modification of surface topology (e.g. selective laser sintering); ablative methods for hard and soft tissue preparation; decontamination of the implant surface or surgical site (laser therapy, or photodynamic therapy); and therapeutic effects to reduce pain, inflammation and promote wound healing (photobiomodulation) [171].…”
Section: Laser Therapy Photodynamic Therapy and Photobiomodulationmentioning
confidence: 99%
“…Since then, numerous studies on a cellular level, laboratory animals, and in humans have confirmed the beneficial effect of laser treatment on wound healing. It has been argued that the best time to apply LLLT is at the stage of cell proliferation [35,36]. It has been shown that LLLT can cause increased bFGF production, which exerts mitogenic activity and induces angiogenesis and tissue repair [37,38].…”
Section: Low Level Laser Therapy (Lllt) and Healing Of Tissuesmentioning
confidence: 99%
“…Moreover, it appeared that the torques required to export osseointegrated implants and the percentages of calcium and phosphorus (ratio by weight) in peri-implant bone were statistically higher in the group of animals that received LLLT. It was concluded that increased levels of calcium and phosphorus demonstrate faster bone maturation, hence faster [35,36]. By applying LLLT with diode laser in in vitro studies, it was shown that there was an increase in cell proliferation, increased adhesion of primary fibroblast cultures and osteoblasts on titanium surfaces, as well as an increase in cell proliferation and differentiation of tumor osteoblasts series (osteoblast like cells), and TGF-b and osteocalcin production by cells of tumor lines [76].…”
Section: Low Level Laser Therapy (Lllt) and Healing Of Tissuesmentioning
confidence: 99%
“…O laser é indicado na Implantodontia para descontaminação da superfície de implantes e tratamento da periimplantite, diminuição de edema, dor e inflamação no pós-operatório, em procedimentos de segundo estágio cirúrgico de implantes submersos (incisão/excisão), cirurgia plástica de tecidos moles e, de maneira experimental, durante o preparo do leito ósseo previamente à instalação de implantes 12,13 . No entanto, é importante o treinamento adequado profissional a respeito do uso do laser a fim de melhorar os resultados clínicos e controlar possíveis complicações, como lesões a estruturas anatômicas nobres e danos à superfície dos implantes.…”
unclassified